Isolation, structure elucidation, and KDD study of (−)-Celosine, a new skeleton with potent anti-atherosclerosis activity. Issue 80 (1st November 2017) - Sun, Zhenliang; Lv, Zhiliang; Hu, Bin; Zhang, Jifa; Du, Peng; Wang, Man; Xiao, Linlin; Yang, Peiming
Abstract : Natural (−)-Celosine was isolated as a novel endocyclicditerpene with an unprecedented skeleton from Celosia cristata L. Abstract : Natural (−)-Celosine was isolated as a novel endocyclicditerpene with an unprecedented skeleton from Celosia cristata L. Its structure was established by comprehensive 1D and 2D NMR spectroscopic analysis in combination with single-crystal X-ray crystallographic diffraction of synthesized (+)-Celosine. (−)-Celosine was expected to have an anti-atherosclerotic activity in vivo, and myeloperoxidase (MPO) expression may be the mechanism underlying this anti-atherosclerotic activity.